Ответы и объяснения

2013-04-04T06:41:17+00:00

(11-3х)/4=(х+13)/(6-х)

ОДЗ:(6-х) не равно 0

          х не равно 6

умножим обе части уравнения на 4(6-х)

(11-3х)*4*(6-х)/4=(х+13)*4*(6-х)/(6-х)

(11-3х)(6-х)=4(х+13)

66-18х-11х+3х^2=4x+52

3x^2-29x-4x+66-52=0

3x^2-33x+14=0

x1,2=[33+/-корень квадратный(33^2-4*14*3)]/(2*3)

x1,2=[33+/-корень квадратный(1089-168)]/6

x1,2=[33+/-корень квадратный(921)]/6

x1=[33+корень квадратный(921)]/6 приблиз равно (33+30,35)/6=10,56

x2=[33-корень квадратный(921)]/6 приблиз равно (33-30,35)/6=0,44